PEMANFAATAN KIAMBANG (Salvinia molesta D. Mitch) UNTUK FITOREMEDIASI LIMBAH ORGANIK PULP DAN KARATS - Iwan Simatupang; Siti Fatonah; Dyah Iriani (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
"> Paper industry produce water wastethat contain organic and inorganic compounds. The efforts to control the pollution caused by waste is carried out using phytoremediationsuch as the use of Salvinia molesta(kiambang). The purpose of this research was to improve the quality of water in liquid organic water and paper pulp. The study used a completely randomized design (CRD) with five dilution treatment 25%, 50%, 75% and 100% and control (0%) for 15 days. Data were analyzed using ANOVA and followed by DMRT at 5% level. The results showedthat kiambang grown on paper and pulp wastecould improve the quality of waste at 25%concentrations, withincreasing DO content from 5 ppm to 16 ppmabove DO content of nomal water. Kiambang plant could absorb organic compounds and improved the value of DO while BOD, COD and TSS didn’t reach the water quality standard yet for all treatments. Howerver, for 25% and 50% consentration gave a closer result to the water quality standard.